Effects of charge on the performance of R290 air conditioner with different expansion devices. (25th July 2018) - Liu, Cichong; Wang, Dandong; Sun, Ziyang; Chen, Liang; Shi, Junye; Chen, Jiangping
Highlights: Different throttling devices are compared in one split air conditioning system. TXV and EEV can help reduce R290 refrigerant charge. The sensitivity of system to R290 charge was investigated under various conditions. Superheat degree influence on R290 system was analyzed. Abstract: Safety is a critical issue when considering R290 as a replacement for R22 in air conditioning and heat pump systems. The R290 charge mass in the domestic system is strictly restricted which means a small amount of leakage would be equivalent to a large percent of refrigerant loss. In this article, the effects of R290 refrigerant charge influences on a split air conditioning system with different throttling devices including capillary tube, thermostatic expansion valve (TXV), and electronic expansion valve (EEV) are experimentally investigated alongside with the indoor temperature, outdoor temperature and indoor air volume flow rates effects. Besides, the effects of superheat degree influences have been studied both theoretically and experimentally. The results suggested a larger superheat degree would have an optimum effect on R290 system performance.